Relation between Vitamin D Level and Knowledge and Attitude Towards Sunlight Exposure among Asthma Outpatients in Surabaya - Amelia Lorensia; Rivan Virlando Suryadinata; Gebriella Ayuni Amir (Global Medical & Health Communication (GMHC), 2019)
Asthma has become one of the health problems in the world. Asthma is characterized by chronic inflammation of the respiratory tract which leads to breathlessness, wheezing, and airflow limitation. Inflammatory reaction in asthma is related to inadequate vitamin D level. Vitamin D is a vitamin produced naturally by the body when exposed to sunlight that has immunomodulatory properties can reduce inflammation. Knowledge and positive attitude to sun exposure are necessary to prevent severe asthma attacks. This was a cross-sectional study involving 26 subjects in a private university in east Surabaya during January–June 2017 that was aimed to determine the relation between vitamin D and knowledge and attitude towards sunlight exposure. Data were collected by measuring the vitamin D level in blood serum and through the use of a questionnaire that consisted of two aspects, level of knowledge and attitude to sun exposure. Chi-square test was used to analyze the relationship between vitamin D level, knowledge, and attitude. No relationship was found between blood vitamin D level of asthma respondents and level of knowledge of sun exposure related to vitamin D (p=0.444, p>0.05). The same was also true for the relationship between blood vitamin D level of asthma respondents and attitude to sun exposure related to vitamin D (p=0.768, p>0.05). The closeness of the relationship between knolwedge and attitude was also relatively low (0.093). In conclusion, there is no correlation between vitamin D level, knowledge, and attitude. In addition, there is also no correlation between knowledge and attitude with low relationship between the two variables. HUBUNGAN KADAR VITAMIN D DENGAN PENGETAHUAN DAN SIKAP TENTANG PAPARAN SINAR MATAHARI PADA PASIEN ASMA RAWAT JALAN DI SURABAYAAsma telah menjadi masalah kesehatan di dunia. Asma ditandai oleh peradangan kronis pada saluran pernapasan yang menyebabkan sesak napas, mengi, dan keterbatasan aliran udara. Reaksi peradangan pada asma terkait dengan kadar vitamin D yang tidak memadai. Vitamin D merupakan vitamin yang diproduksi secara alami oleh tubuh ketika terkena sinar matahari yang memiliki sifat imunomodulator dapat mengurangi peradangan. Pengetahuan dan sikap positif terhadap paparan sinar matahari diperlukan untuk mencegah risiko keparahan asma. Penelitian ini menggunakan metode cross-sectional yang melibatkan 26 subjek di sebuah universitas swasta di Surabaya Timur pada Januari–Juni 2017 yang bertujuan menentukan hubungan vitamin D dengan pengetahuan dan sikap terhadap paparan sinar matahari. Data dikumpulkan dengan mengukur kadar vitamin D dalam serum darah dan melalui penggunaan kuesioner yang terdiri atas dua aspek, tingkat pengetahuan dan sikap terhadap paparan sinar matahari. Uji chi-square digunakan untuk menganalisis hubungan antara kadar vitamin D, pengetahuan, dan sikap. Tidak ada hubungan yang ditemukan antara kadar vitamin D darah responden asma dan tingkat pengetahuan paparan sinar matahari yang terkait dengan vitamin D (p=0,444; p>0,05). Hal yang sama juga berlaku untuk hubungan antara kadar vitamin D darah responden asma dan sikap terhadap paparan sinar matahari yang terkait dengan vitamin D (p=0,768; p>0,05). Kedekatan hubungan antara pengetahuan dan sikap juga relatif rendah (0,093). Simpulan, tidak ada hubungan antara kadar vitamin D, pengetahuan, dan sikap. Selain itu, juga tidak ada hubungan yang rendah antara pengetahuan dan sikap.